Evolution of a dislocation structure during the growth silicon single crystals of n– and p–type - Azarenkov, N.A.; Semenenko, V.E.; Stervoyedov, N.G. (Вопросы атомной науки и техники, 2020)
The kinetics of the formation of perfect n– and p–type silicon single crystals is considered. The peculiarity of the formation of point and linear defects in the process of a controlled phase transformation of a liquid–solid is established. The effect of supersaturation by vacancies of the direction of predominant growth and concentration of impurities on the formation and removal of edge and screw dislocations is determined. The effect of linear defects on the scattering and recombination of mobile current carriers is revealed. The possibilities of increasing the stability and efficiency of silicon semiconductor devices are discussed. Розглянута кінетика формування досконалих монокристалів кремнію n– та p–типів. Встановлена особливість утворення точкових і лінійних дефектів у процесі контрольованого фазового перетворення рідина–тверде тіло. Визначено вплив пересичення вакансіями напрямку переважного зростання і концентрації домішок на процес утворення і видалення крайових і гвинтових дислокацій. З’ясовано роль лінійних дефектів на розсіяння і рекомбінацію рухомих носіїв струму. Обговорюються можливості підвищення стабільності роботи, ККД кремнієвих напівпровідникових приладів. Рассмотрена кинетика формирования совершенных монокристаллов кремния n– и p–типов. Установлена особенность образования точечных и линейных дефектов в процессе контролируемого фазового превращения жидкость–твердое тело. Определено влияние пересыщения вакансиями направления преимущественного роста и концентрации примесей на процесс образования и удаления краевых и винтовых дислокаций. Выяснена роль линейных дефектов на рассеяние и рекомбинацию подвижных носителей тока. Обсуждаются возможности повышения стабильности работы, КПД кремниевых полупроводниковых приборов.